A Clinical Application of Bion's Concepts, Volume 2 : Analytic Function and the Function of the Analyst. - Sandler, Sandler (Karnac Books, 2011)
'In this magisterial work Paulo Sandler continues to distinguish himself as a foremost scholar on the works of Bion. Already well known for his encyclopedic zeal, this present book continues Sandler's tireless search of Bion's contributions by this noteworthy clinical application of Bion's ideas. A major feature of Sandler's approach to studying Bion has been to contextualise the background of Bion's assumptions. In so doing, he extensively investigates the cultural and historical antecedents, especially including the philosophical and scientific points of view. From them Sandler selects Romant.